Which Language of Nature for Berkeley’s God? - Berchielli, Laura (Philosophy & theology, 2024)
In An Essay towards a New Theory of Vision, Berkeley compares vision to a language, and in Treatise on the Principles of Human Knowledge, he compares nature’s methods to a divine language. In this article, I firstly study the characteristics of the notion of language used by Berkeley in these two contexts, as well as the scope of the two analogies. Based on the results of this study, I show how, contrary to what is generally asserted, the notions of the ‘language of nature’ in the New Theory of Vision and the Principles have a different and, in some respects, incompatible meaning, status and purpose. I then suggest how all the amendments and deletions made to the passages dealing with the language of nature in the works and new editions published during the 1730s can be read in the light of this incompatibility and Berkeley’s efforts to prevent the risk of a drift towards materialism and atheism linked to a consideration of nature as a language.